2021
DOI: 10.1097/aco.0000000000000983
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for pediatric periprocedural care

Abstract: Purpose of reviewCommercial availability of virtual reality headsets and software has exponentially grown over the last decade as it has become more sophisticated, less expensive, and portable. Although primarily used by the general public for entertainment, virtual reality has been adopted by periprocedural clinicians to improve patient experiences and treatments. The purpose of this review is to explore recently reported evidence for virtual reality effectiveness for pediatric periprocedural care and discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…The majority of providers surveyed believe that VR helps their clients/patients progress in treatment compared to similar therapy without VR. These subjective findings corroborate previous studies that have shown the effectiveness of VR in treatment of phobias [4,11,12,[26][27][28], anxiety [5,6,10,13,20,29], PTSD [2,7,14], addictions [8,30,31], and pain management [2,3,15,16,18,32].…”
Section: Key Findingssupporting
confidence: 90%
“…The majority of providers surveyed believe that VR helps their clients/patients progress in treatment compared to similar therapy without VR. These subjective findings corroborate previous studies that have shown the effectiveness of VR in treatment of phobias [4,11,12,[26][27][28], anxiety [5,6,10,13,20,29], PTSD [2,7,14], addictions [8,30,31], and pain management [2,3,15,16,18,32].…”
Section: Key Findingssupporting
confidence: 90%
“…Non-pharmacological interventions such as parental acupuncture, clowns/clown doctors, playing videos of the child’s choice, low sensory stimulation, and hand-held video games have promising potential for reducing anxiety and improving cooperation during preoperative sedation [ 70 ]. However, these methods do not usually provide adequate relief and thus, pharmacological sedation and analgesia are necessary [ 71 ]. Wang et al suggested that clinical programs that supplement virtual reality can be considered in pediatric periprocedural care [ 71 ].…”
Section: Perioperative Anesthetic Phasesmentioning
confidence: 99%
“…However, these methods do not usually provide adequate relief and thus, pharmacological sedation and analgesia are necessary [ 71 ]. Wang et al suggested that clinical programs that supplement virtual reality can be considered in pediatric periprocedural care [ 71 ]. By definition, pediatric patients with “special needs” (SN) are children suffering from psycho-physical disorders and relational and cognitive problems [ 1 , 2 ].…”
Section: Perioperative Anesthetic Phasesmentioning
confidence: 99%
“…Also, due to the visual contact with their surroundings, children are less likely to experience nausea, also known as "cybersickness." 19 Recent reports suggest that AR is a promising intervention to alleviate preoperative anxiety in children. 16 However, further empirical evidence-based on standardized randomized-controlled trials with larger samples-is needed to establish whether AR could serve as an efficient and safe non-pharmacological solution to managing preoperative anxiety in patients.…”
Section: Introductionmentioning
confidence: 99%
“…AR is unique in its ability to blend the unfamiliar surroundings of the perioperative setting of the hospital with playful holograms. Also, due to the visual contact with their surroundings, children are less likely to experience nausea, also known as “cybersickness.” 19 …”
Section: Introductionmentioning
confidence: 99%